Design and Construction of a Closed House Chicken Coop with a Punos 313 Based Temperature Control and Monitoring System - Devit Rahmawati; Eko Joko Guntoro (Baselang, 2023)
The public's need for food derived from Broiler chickens is increasing. To meet this increase, livestock businesses began to create Closed House type chicken coops for breeding Broiler Chickens or DOC (Day Old Chicken) Chicken Seeds. Where the growth and development of broiler chickens in regular/open house cages is very susceptible to cage temperature because they often find it difficult to control and monitor the temperature of the cage so that it remains ideal. To overcome this, this research builds a system that can control temperature to obtain the ideal temperature in the broiler chicken coop using a Punos 313-based temperature control and monitoring system so that farmers can control and monitor the temperature of the chicken coop remotely. Punos 313 is a tool for recording temperature and humidity data in the cage and then transmitting the data to the system using SKOV. The results of this research show that the system is able to control temperature and monitor temperature conditions in the cage remotely.